Innovative Approaches in the Treatment of Pancreatic Cancer: The Role of CAR T-Cell Therapy - Kuźniar, Jakub; Chrzanowska, Emilia Gabriela; Szlążek, Julia; Ząbek, Adam Jan; Zagalska, Michalina; Turek, Marta; Tamborski, Tomasz; Grzebinoga, Adam; Roguska, Barbara; Kuźniar, Anna Katarzyna (Journal of Education, Health and Sport, 2025)
Introduction Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal gastrointestinal cancers, marked by late diagnosis, rapid progression, and resistance to treatment, resulting in a five-year survival rate below 10%. Chimeric antigen receptor T-cell (CAR T-cell) therapy has shown success in hematologic malignancies, sparking interest in its potential for solid tumors like PDAC. This paper reviews current knowledge on CAR T-cell therapy in PDAC, focusing on challenges, future prospects, and available studies. Methodology This literature review is based on a search of PubMed and Google Scholar for publications from the last 10 years. Fifty sources, including original studies, reviews, and clinical reports, were analyzed with focus on mechanisms of action, preclinical/clinical outcomes, safety, and toxicity. Results Studies show that CAR T-cell therapy can stabilize PDAC and even induce remission when targeting tumor-specific antigens. However, major obstacles remain: poor tumor penetration, toxicity (e.g., cytokine release syndrome), and "on-target, off-tumor" effects. Clinical trials report modest CAR T-cell expansion and persistence, suggesting the need for improved design and strategies. Conclusions While CAR T-cell therapy for PDAC is promising, its effectiveness is hindered by the tumor microenvironment and side effects. Future directions include better antigen targeting, modified CAR constructs, combination therapies, and personalized or allogeneic CAR T-cell approaches to enhance outcomes in this difficult-to-treat cancer.